Mycorrhizal Dependency of Alcaparro (Senna pistaciifolia Kunth) at Three Concentrations of Soil Solution Phosphorus (2015)
Abstract. A greenhouse bioassay was carried out to determine the mycorrhizal dependency of alcaparro (Senna pistaciifolia Kunth). A randomized complete experimental design was employed, with six treatments in a factorial arrangement 3x2; the treatments consisted of three levels in soil solution phosphorus (P) (0.002, 0.02, and 0.2 mg L-1) combined with two levels of mycorrhizal inoculation either uninoculated or inoculated with Glomus agreggatum. The variables studied were leaf P content as a function of time, shoot dry matter, shoot P content, mycorrhizal colonization of roots, and the mycorrhizal dependency (MD). The results indicate that the leaf P content increased significantly with the mycorrhizal inoculation in alcaparro to 0.02 mg L-1 after the second sampling days, but not in the other soil P levels. Likewise, shoot dry weight increased significantly at 0.02 mg L-1. On the other hand, the total plant P content increase at all levels of soil available P. The mycorrhizal colonization in alcaparro roots was 11, 23, and 0% at 0.02, 0.002 and 0.2 mg of P L-1, respectively. The MD for alcaparro was 32%, which allow classify this specie as moderately dependent on the mycorrhizal association. /  Resumen. Se realizó un bioensayo en invernadero para determinar la dependencia micorrizal de alcaparro (Senna pistaciifolia Kunth). Se utilizó un diseño experimental completamente randomizado. Los tratamientos se arreglaron en un factorial 3x2, estos consistieron en la combinación de tres niveles de P en la solución del suelo (0.002, 0.02 y 0.2 mg L-1) y 2 niveles de inoculación micorrizal (inoculado y no inoculado) con el hongo Glomus agreggatum. Se emplearon como variables respuesta el contenido de P foliar en función del tiempo; al momento de la cosecha, se determinaron la masa seca aérea, el P total en la parte aérea y la colonización micorrizal. Los resultados indican que el contenido de P foliar a 0.02 mg L-1 en el segundo muestreo aumentó significativamente con la inoculación micorrizal, pero no en los otros niveles de P. La masa seca aérea también creció significativamente a 0.02 mg L-1. De otro lado, el contenido de P total absorbido se incrementó significativamente en todos los niveles de P. La colonización micorrizal en las raíces del alcaparro fue de 11, 23 y 0 % para los niveles de 0.002, 0.02 y 0.2 mg L-1, respectivamente. La dependencia micorrizal fue del 32 %, por lo que esta especie se clasifica como moderadamente dependiente.